2022
DOI: 10.3390/life12101479
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Cadmium Stress by Silicon Supplementation in Peas by the Modulation of Morpho-Physio-Biochemical Variables and Health Risk Assessment

Abstract: Agricultural soil quality degradation by potentially toxic elements, specifically cadmium (Cd), poses a significant threat to plant growth and the health of humans. However, the supplementation of various salts of silicon (Si) to mitigate the adverse effect of Cd on the productivity of peas (Pisum sativum L.) is less known. Therefore, the present investigation was designed to evaluate the exogenous application at various levels (0, 0.50, 1.00 and 1.50 mM) of silicate compounds (sodium and potassium silicates) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Galal et al (2021) investigated the accumulation potential of heavy metals in various organs of field pea and observed significant reductions in fresh and dry weights of pea plants, as well as pod production, in polluted (20.4 mg Cd/kg soil) solis compared to nonpolluted (0.2 mg Cd/kg soil) ones. Furthermore, Batool et al (2022) found that Cd pollution significantly decreased traits related to growth, phenology, and biomass of pea plants, while also markedly increasing Cd contents in roots, shoots, and seeds compared to the control. Additionally, Cd contamination has been shown to highly affect the biomass and productivity of Solanum lycopersicum L. plants grown in soil irrigated with untreated industrial wastewater …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Galal et al (2021) investigated the accumulation potential of heavy metals in various organs of field pea and observed significant reductions in fresh and dry weights of pea plants, as well as pod production, in polluted (20.4 mg Cd/kg soil) solis compared to nonpolluted (0.2 mg Cd/kg soil) ones. Furthermore, Batool et al (2022) found that Cd pollution significantly decreased traits related to growth, phenology, and biomass of pea plants, while also markedly increasing Cd contents in roots, shoots, and seeds compared to the control. Additionally, Cd contamination has been shown to highly affect the biomass and productivity of Solanum lycopersicum L. plants grown in soil irrigated with untreated industrial wastewater …”
Section: Introductionmentioning
confidence: 99%
“…19−21 Indirect evidence from global data indicates that legumes accumulate Cd within the range of 0.08−0.28 mg/kg fruit/ seed dry weight, surpassing the maximum permissible values recommended by FAO/WHO for heavy metals in vegetables (<0.02 mg Cd/kg DW). 22,23 Several studies, including those by Galal et al (2021), 24 Batool et al (2022), 25 and others, 26−29 have illustrated the detrimental effects of Cd contamination on growth and yield parameters of pea cultivars, along with other pulses like pigeonpea, 30 as well as globally significant crops such as wheat 31 and tomatoes. 32 Galal et al ( 2021) 24 investigated the accumulation potential of heavy metals in various organs of field pea and observed significant reductions in fresh and dry weights of pea plants, as well as pod production, in polluted (20.4 mg Cd/kg soil) solis compared to nonpolluted (0.2 mg Cd/kg soil) ones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy metals are non-biodegradable trace elements and are considered harmful to plants, animals, and humans [ 1 ]. Some heavy metals are categorized as essential heavy metals, which are somehow required for plant growth [ 2 ], while others are classified as non-essential heavy metals, which are not required for plant growth [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%